Systematic discounting in climate policy analysis - Stefan Bayer; Dieter Cansier (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1996)
We investigate the systematic intergenerational discounting of climate policy on basis of the neo-classical benefit-cost analysis. Reference point is the Ramsey-rule which results from optimal growth theory. The agents live infinitely long. This signifies that intergenerational comparisons do not exist. The resulting rates - the pure rate of time preference, the growth discount rate, and the opportunity cost rate - are examined in detail for their legitimacy regarding intergenerational comparisons. One result of our examination is that utility-based pure time preference rates cannot be justified ethically in intergenerational comparisons. Under certain conditions, the consumption based growth discount rate can be used where intergenerational aspects are concerned. If we discount long-term climate policy effects by using an investment-based opportunity cost rate, we further have to analyze the calculation of consumption equivalents. If we adjust the planning horizon to the life expectancy of human beings, a realistic discounting method would be to use an OLG-model. This method allows each living generation to discount intragenerationally with the sum of the pure time preference rate and the growth discount rate. As soon as intergenerational effects exist, one may only use the growth discount rate to calculate present values.
Keywords: 330; Benefit-cost analysis; climate policy; discounting; overlapping generations; shadow price of capital; Klimawandel; Umweltökonomik; Kosten-Nutzen-Analyse; Overlapping Generations; Soziale Diskontrate; Theorie